Israel's civil society 2023 from protest to aid provision – a serving elite perspective - Gidron, Benjamin; Katz, Hagai (Frontiers in Sociology, 2024)
The year 2023 in Israel started with illiberal constitutional change efforts by the new right-wing government and concluded with a brutal attack by Hamas terrorists and the subsequent war. Both occurrences galvanized two massive surges of civil society activism. The first was a mass protest that impeded the government's undemocratic legislation. The second was a large-scale mobilization to support a variety of populations affected by the war, providing services and goods that supplanted the failed governmental crisis response. Using a Serving Elite perspective and elaborating on this concept in the Israeli context, the paper analyzes the organizations that transitioned overnight from protest to service delivery. While these are two known roles played by civil society in general, such a transition from protest to support within the same organization is unusual, if at all existent. The paper analyses nineteen (19) in-depth interviews with leaders of 10 prominent organizations active in the protest and the aid phases. It explores their participants, forms of organizing, activities, ideologies, and interconnections, particularly emphasizing the transition. Thematic analysis of the interviews revealed the emergence of a new Serving Elite in the making, liberal in orientation, and developed during the crises. This perspective provides an opportunity to highlight processes deeply embedded in Israel's social, political, and cultural landscapes, changing elites and power relations, and Israel's culture of entrepreneurship. It also provides a framework for analyses of serving elites in other countries.